Analisis Perilaku Praktek Nelayan Dalam Penangkapan Ikan Ditinjau Dari Perspektif Hukum Ekonomi Islam Di Kecamatan Paciran Kabupaten Lamongan - Zahrotul Maásah (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Not many people discuss fishermen, but the reality of their lives, particularly for small-scale or traditional fishermen, involves facing the challenges of the sea's waves and winds to procure fresh fish. This catch is eagerly awaited by communities as a staple in our daily nutrition. The lives of these fishermen and their families appear imbalanced compared to their struggle against the vast, unbounded sea. What they invest as provisions for fishing often surpasses their earnings. Hence, this becomes one of the reasons they employ whatever means necessary to maximize their catch, often without considering the potential repercussions of their actions on the sea's ecosystem. These practices are unequivocally prohibited by the law, specifically detailed in Ministerial Decree No. 2 of 2015, which prohibits the use of trawl nets and seine nets within Indonesia's Fishery Management Zones (WPP). Islam regards the act of earning a livelihood as an act of worship and even a duty for every adult to fulfill their needs and those of their families. However, Islam also prohibits causing harm to the Earth. One of the fishing techniques frequently employed by fishermen in the Paciran district of Lamongan Regency is the "payang" net. In line with Islamic economic principles, the use of the payang net also falls within the category of forbidden fishing gear according to Ministerial Decree No. 2 of 2015. This is due to the nature of this gear being non-selective in capturing fish, often resulting in damage to coral reefs. As a result, the growth of the marine ecosystem becomes sluggish, requiring a prolonged duration for the recovery of fish populations in the sea.